Effect of low-frequency vibration on workpiece in EDM processes - Prihandana, Gunawan Setia; Mahardika, Muslim; Abd Shukor, Mohd Hamdi; Mitsui, Kimiyuki (Springer Verlag (Germany), 2011)
High-frequency vibration aided EDM has become one of the ways to increase material removal rate in EDM process, due to the flushing effect caused by vibration. However, utilizing high-frequency vibration, especially in ultrasonic range consumes a lot of setup cost. This work presents an attempt to use a low-frequency vibration on workpiece of stainless steel (SS 304) during EDM process. The workpiece was vibrated with variations of low-frequency and low-amplitude. The results show that the application of low-frequency vibration in EDM process can be used to increase the material removal rate, and decrease the surface roughness and tool wear rate.